Openness to messages about English as a foreign language: Working with learners to uncover purpose to study. (January 2019) - Sampson, Richard J.
As a compulsory classroom subject in an environment in which it is rarely used, English as a foreign language might seem to have very little connection to students' present or future lives. There may be a disconnect between various circulating messages about English, and experiences of little day-to-day English use. This article presents understandings that evolved through an action research project with undergraduate students in Japan. The study was instigated due to a gap between the expectations of industry for graduates' English abilities, and perceptions by learners. Data were collected from 48 Japanese science and technology students in two of the author's first-year, compulsory English classes. Change-action activities encouraged participants to engage with messages about English they carried with them into the classroom. Analysis revealed students to be very capable of describing and discussing detailed discourses absorbed from past teachers, family and peer-group members, and society and the media. These ideas had varying motivational and affective resonance for learners. Over the research, the faculty of change-action activities to foster reflection, share understandings and introduce new information seemed to reduce the discrepancy with industry expectations.